“I always feel like I have to rush…”: pet owner and small animal veterinary surgeons’ reflections on time during preventative healthcare consultations in the United Kingdom - Belshaw, Zoe; Robinson, N.J.; Dean, Rachel S.; Brennan, Marnie L. (MDPI, 2018)
Canine and feline preventative healthcare consultations can be more complex than other consultation types, but they are typically not allocated additional time in the United Kingdom (UK). Impacts of the perceived length of UK preventative healthcare consultations have not previously been described. The aim of this novel study was to provide the first qualitative description of owner and veterinary surgeon reflections on time during preventative healthcare consultations. Semi-structured telephone interviews were conducted with 14 veterinary surgeons and 15 owners about all aspects of canine and feline preventative healthcare consultations. These qualitative data were thematically analysed, and four key themes identified. This paper describes the theme relating to time and consultation length. Patient, owner, veterinary surgeon and practice variables were recalled to impact the actual, versus allocated, length of a preventative healthcare consultation. Preventative healthcare consultations involving young, old and multi-morbid animals and new veterinary surgeon-owner partnerships appear particularly susceptible to time pressures. Owners and veterinary surgeons recalled rushing and minimizing discussions to keep consultations within their allocated time. The impact of the pace, content and duration of a preventative healthcare consultation may be influential factors in consultation satisfaction. These interviews provide an important insight into the complex nature of preventative healthcare consultations and the behaviour of participants under different perceived time pressures. These data may be of interest and relevance to all stakeholders in dog and cat preventative healthcare.